2012
DOI: 10.1016/j.clim.2011.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Live Attenuated Influenza Virus (LAIV) induces different mucosal T cell function in nonsmokers and smokers

Abstract: Smokers are more susceptible to respiratory infections, including influenza. To explore the effect of smoking on influenza-induced responses within the nasal mucosa, we have developed a protocol using inoculation with live attenuated influenza virus (LAIV) vaccine followed by sampling of the nasal mucosa. Mucosal cell populations were harvested through superficial biopsy of the nasal inferior turbinate pre and post LAIV inoculation and analyzed using flow cytometry. The majority of nasal biopsy CD45+ immune ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 21 publications
(28 reference statements)
1
27
0
Order By: Relevance
“…These studies demonstrated that smokers inoculated with liveattenuated influenza virus (LAIV) vaccine had reduced cytotoxic NK cells and markers of activated NK cells in their nasal lavage (17). In a similar study, we demonstrated that LAIVinduced recruitment of ␥/␦ T cells into the nasal mucosa is impaired in smokers (16). Thus smoking-induced gene silencing of ULBP3 in NECs could lead to decreased NK cell and ␥/␦ T cell function in the nasal mucosa in the context of viral infection and result in impaired ability to recognize and eliminate virus-infected host cells.…”
Section: Discussionsupporting
confidence: 53%
“…These studies demonstrated that smokers inoculated with liveattenuated influenza virus (LAIV) vaccine had reduced cytotoxic NK cells and markers of activated NK cells in their nasal lavage (17). In a similar study, we demonstrated that LAIVinduced recruitment of ␥/␦ T cells into the nasal mucosa is impaired in smokers (16). Thus smoking-induced gene silencing of ULBP3 in NECs could lead to decreased NK cell and ␥/␦ T cell function in the nasal mucosa in the context of viral infection and result in impaired ability to recognize and eliminate virus-infected host cells.…”
Section: Discussionsupporting
confidence: 53%
“…We and others have shown that cigarette smoking modifies mucosal host defense, yet the specific mechanisms mediating this effect remain unclear (19,20,22,36). A hallmark of cigarette smoking is a shift in the protease/antiprotease balance in favor of protease expression and activity (1,28,53).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that the persistence of immunity to hepatitis B in cigarette smokers was lower than nonsmokers [19]. It has been recently reported that the immune response (within the nasal mucosa) to attenuated influenza virus vaccine were suppressed in smokers as compared to nonsmokers [20]. Furthermore, it has been reported that cigarette smokers are susceptible to infection and sepsis [21].…”
Section: Figure 1: Distribution Of Subjects According To Anti-tetanusmentioning
confidence: 99%